2015
DOI: 10.1021/acsnano.5b01939
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine for Cancer Immunotherapy: Tracking Cancer-Specific T-Cellsin Vivowith Gold Nanoparticles and CT Imaging

Abstract: Application of immune cell-based therapy in routine clinical practice is challenging due to the poorly understood mechanisms underlying success or failure of treatment. Development of accurate and quantitative imaging techniques for noninvasive cell tracking can provide essential knowledge for elucidating these mechanisms. We designed a novel method for longitudinal and quantitative in vivo cell tracking, based on the superior visualization abilities of classical X-ray computed tomography (CT), combined with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(143 citation statements)
references
References 50 publications
(108 reference statements)
1
142
0
Order By: Relevance
“…In a comparison study of CT imaging to fluorescence imaging, T cells dual-labeled with AuNPs and reporter gene overexpressing green fluorescent protein (GFP) demonstrated si milar trends of T cells distribution and movement in vivo. The incorporated AuNPs also acted as anti-tumor agents in this system, in that targeted T-cells with AuNPs-labeling significantly inhibited tumor progression compared to nontargeted or nontreated controls or AuNPs alone [64] .…”
Section: Computed Tomography Contrast Agentbased Labelingmentioning
confidence: 99%
“…In a comparison study of CT imaging to fluorescence imaging, T cells dual-labeled with AuNPs and reporter gene overexpressing green fluorescent protein (GFP) demonstrated si milar trends of T cells distribution and movement in vivo. The incorporated AuNPs also acted as anti-tumor agents in this system, in that targeted T-cells with AuNPs-labeling significantly inhibited tumor progression compared to nontargeted or nontreated controls or AuNPs alone [64] .…”
Section: Computed Tomography Contrast Agentbased Labelingmentioning
confidence: 99%
“…AuNP were incubated with T cells transformed to express a melanoma-specific T-cell receptor before being injected intravenously into mice bearing human melanoma xenografts. The internalized particles were tracked using CT and cells were found to accumulate in the melanomas, while nontransformed cells did not [68].…”
Section: Cancer Targeted Gold Nanoparticles Formulationsmentioning
confidence: 99%
“…Meir et al have shown in melanoma-bearing mice that labeled GNPs can track tumor-specific T-cells using whole body CT. This approach is a next-generation imaging technique as well as a new tool in immunotherapy (59).…”
Section: Nanomedicine For Melanoma Detection and Treatmentmentioning
confidence: 99%